1998
DOI: 10.1177/00220345980770091101
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Characteristics of Resin-modified Glass-ionomer Materials: A Study on Fluid Permeability Using Confocal Fluorescence Microscopy

Abstract: The tooth interface with resin-modified glass-ionomer cements (RM GICs) is poorly understood. This study examined the interface, especially with dentin. Cervical cavities in extracted teeth were restored with Fuji II LC, Vitremer, Photac-Fil, or a conventional GIC, Fuji Cap II. Fluorescent dye was placed in the pulp chambers for 3 hrs before the specimens were sectioned. Examination of the tooth/material interface with a confocal microscope showed that dye uptake by the restoration varied among materials. A "s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 12 publications
1
68
1
4
Order By: Relevance
“…However, the experimental evidence seems equivocal. Some workers [25][26][27] have demonstrated resin tags in the dentinal tubules, while others [28][29][30] did not appear to do so. The 'hybrid layer' of resin-dentine bonding was apparently observed by Pereira et al, 10,27 but could not be identified by Lin et al 25 or by Ramos and Perdigão.…”
Section: Bonding Mechanismmentioning
confidence: 99%
“…However, the experimental evidence seems equivocal. Some workers [25][26][27] have demonstrated resin tags in the dentinal tubules, while others [28][29][30] did not appear to do so. The 'hybrid layer' of resin-dentine bonding was apparently observed by Pereira et al, 10,27 but could not be identified by Lin et al 25 or by Ramos and Perdigão.…”
Section: Bonding Mechanismmentioning
confidence: 99%
“…In the resin modified glass-ionomers the acid/base reaction will initially be a little slower than it would have been in a conventional glass-ionomer because the HEMA has replaced some of the normal water content and water is an essential component of the acid/base reaction. 7 At the same time, because of the incorporation of traces of camphorquinone and a tertiary amine in the formula, irradiation of the surface layer will initiate polymerization of the HEMA and this will be complete in less than one minute. This reaction is quite separate from the acid/base reaction but a high degree of cross linking will occur between the two matrices as the acid/base reaction continues.…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…In the unloaded specimens treated with Vitrebond Plus, elemental analysis ( Fig. 6C-EDX) showed P and Ca as main components, but lower fractions of Al, Na and Sr were also detected, which became integrated in this porous, nonparticulate, poly(HEMA)-rich hydrogel layer [47], the absorption layer [23]. This 7-10 µm thick structure [10] was first reported by Watson and Barlett (1994) [48] , and contains some of the ions released by the initial acid-base glass-ionomer reaction between the fluoro-aluminosilicate glass particles, hydroxyapatite and polyacids and is crucial for mediating the bond between RMGICs and dentin [10].…”
Section: Resultsmentioning
confidence: 99%
“…At the bottom of the absorption layer, hydroxyapatite that remained attached to individual collagen fibrils upon application of RMGIC (Vitrebond Plus) formed receptors for primary chemical bonding with polyalkenoic acids incorporated into the materials [16,50]. The deposition of this submicrom phase over the hybrid layer has been evidenced and can thus be regarded as a sub-layer of the earlier-documented absorption layer [23], identified as gel phase, gray intermediate or multilocular phase [16], which buffers the low pH [6].…”
Section: Resultsmentioning
confidence: 99%